2017
DOI: 10.1200/jco.2016.69.2962
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy to Predict the Result of Primary Cytoreductive Surgery in Patients With Advanced Ovarian Cancer: A Randomized Controlled Trial

Abstract: Purpose To investigate whether initial diagnostic laparoscopy can prevent futile primary cytoreductive surgery (PCS) by identifying patients with advanced-stage ovarian cancer in whom > 1 cm of residual disease will be left after PCS. Patients and Methods This multicenter, randomized controlled trial was undertaken within eight gynecologic cancer centers in the Netherlands. Patients with suspected advanced-stage ovarian cancer who qualified for PCS were eligible. Participating patients were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 38 publications
4
81
0
15
Order By: Relevance
“…Recent studies have proposed that laparoscopy can be utilized for identifying malignancy/benignancy in adnexal masses, or utilized as a staging and second-look procedure for ovarian cancer. 7,8 The purpose of laparoscopy in this patient was to detect unknown primary lesions of metastatic adenocarcinoma. If a primary lesion is identified, laparoscopy is converted to a suitable surgery for malignancy; otherwise, chemotherapy is immediately initiated postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have proposed that laparoscopy can be utilized for identifying malignancy/benignancy in adnexal masses, or utilized as a staging and second-look procedure for ovarian cancer. 7,8 The purpose of laparoscopy in this patient was to detect unknown primary lesions of metastatic adenocarcinoma. If a primary lesion is identified, laparoscopy is converted to a suitable surgery for malignancy; otherwise, chemotherapy is immediately initiated postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The role of diagnostic laparoscopy to determine the possibility of primary optimal cytoreductive surgery in patients with advanced epithelial ovarian cancer has been reported. In a randomized, controlled trial involving patients with suspected advanced ovarian cancer, diagnostic laparoscopy was reported to reduce the number of futile laparotomies and be reasonable to proceed with primary cytoreductive surgery if cytoreduction to less than 1 cm of residual disease seems feasible [39]. Moreover, the same group has reported that diagnostic laparoscopy did not increase total direct medical health care costs or adversely affect complications or quality of life [40], suggesting that laparoscopy might be a potential diagnostic procedure in advanced epithelial ovarian cancer, although port-site metastasis occurs in 16-47% of cases, and the prognostic impact is still controversial [41].…”
Section: Discussionmentioning
confidence: 99%
“…The RT = 0 results were 87.5% for the PDS group and 59.8% for the IDS group, with a median OS of 65.3 months, compared to the IDS group's median OS of 37.8. Moreover, Rutten et al [39] recently published the results of a multicenter randomized trial in which they investigated whether diagnostic laparoscopy could prevent futile laparotomies at PDS by identifying patients with advanced-stage EOC in whom > 1 cm of residual disease would be left after PDS. They compared 102 patients assigned to laparoscopy and 99 patients who received PDS and observed a 10% rate of futile laparotomies in the laparoscopy group compared to 39% in the PDS group (RR 0.25, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%